1996
DOI: 10.1088/0268-1242/11/5/010
|View full text |Cite
|
Sign up to set email alerts
|

Free and bound excitons in thin wurtzite GaN layers on sapphire

Abstract: Free and bound excitons have been studied by photoluminescence in thin (1-10 µm) wurtzite-undoped GaN, n-type GaN:Si as well as p-type GaN:Mg and GaN:Zn layers grown by metal-organic chemical vapour phase deposition (MOCVD). An accurate value for the free A exciton binding energy and an estimate for the isotropically averaged hole mass of the uppermost 9 valence band are deduced from the data on undoped samples. The acceptor-doped samples reveal recombination lines which are attributed to excitons bound to Mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
40
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(46 citation statements)
references
References 31 publications
(38 reference statements)
6
40
0
Order By: Relevance
“…described by the empirical Varshni model 59 or is in more detail modeled by Vina et al 60,61 who apply the Bose-Einstein model and obtain a more reliable description for lower temperatures. The bound excitons in GaN also experience such a red shift of their luminescences but due to their localization this effect is weaker 34,54,55 and cannot clearly be resolved in the analyzed temperature window for a GaN:Mg sample with spectral linewidths of ∼ 5 meV. However, the different evolution of the intensity and the spectral position of the bound and free excitonic transitions still allows their identification.…”
Section: Determination Of the Activation Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…described by the empirical Varshni model 59 or is in more detail modeled by Vina et al 60,61 who apply the Bose-Einstein model and obtain a more reliable description for lower temperatures. The bound excitons in GaN also experience such a red shift of their luminescences but due to their localization this effect is weaker 34,54,55 and cannot clearly be resolved in the analyzed temperature window for a GaN:Mg sample with spectral linewidths of ∼ 5 meV. However, the different evolution of the intensity and the spectral position of the bound and free excitonic transitions still allows their identification.…”
Section: Determination Of the Activation Energiesmentioning
confidence: 99%
“…Zn 51,54 or Be. and τ D2,A2 which is further supported by the determined activation energies E act from section IV.…”
mentioning
confidence: 99%
“…A number of authors have shown that this strain is clearly evidenced by shifts in the photoluminescence ͑PL͒, photoreflectance ͑PR͒, and reflectance ͑R͒ line positions. [2][3][4][5][6][7][8][9][10] It was shown in Ref. 9 that the energy of the free exciton associated with the top valence band (E A ) varies linearly with the in-plane and axial components of the strain tensor.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the lack of high-quality bulk crystals with large size, GaN are usually grown on foreign substrates including sapphire, SiC, silicon, and so on [1][2][3]. This heteroepitaxy gives rise to a homogeneous strain field mainly in consequence of the thermal expansion mismatch.…”
mentioning
confidence: 99%